THE EFFECT OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON CAREER DECISION MAKING OF VOCATIONAL HIGH SCHOOL STUDENTS - Yanuar, Diki Muhammad; Wahono, Puji; Suherdi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine The Effect of Emotional Intelligence and Self-Efficacy on The Career Decision Making of Class XII Students of SMK Negeri 14 Jakarta. The method used is a survey method with a quantitative approach through statistical analysis using multiple linear regression with the IBM SPSS version 24.0 program tool. The sampling technique in this study uses Proportional Random sampling or proportional random sampling. The population used was 239 students with a sample size of 139 students using the Slovin formula with an error rate of 5%. Data collection uses survey results through filling out a questionnaire or questionnaire and using a Likert scale. Furthermore, the data analysis technique in this study consists of instrument test (validity and reliability); analysis requirement test (normality test and linearity test); classical assumption test (multicollinearity test and heteroscedasticity test); and hypothesis testing (F test, T test, and determination coefficient test). Based on the results of this study indicate that emotional intelligence affects career decision-making; Self-efficacy affects career decision-making; Emotional intelligence and self-efficacy together affect career decision-making.